Synthesis and functionalization of polymer networks via germane–ene chemistry. Issue 22 (9th May 2017) - Guterman, Ryan; Harrison, Tristan D.; Gillies, Elizabeth R.; Ragogna, Paul J.
Abstract : Germane–ene polymer networks are prepared by utilizing Ge–H bonds with suitable crosslinkers; the materials are ideally suited for post polymer functionalization. Abstract : Diphenylgermane was polymerized with a multifunctional olefin to create a polymer network possessing pendant Ge–H functional groups within the material. Unlike silanes, which do not efficiently undergo radical mediated hydrosilylation reactions, we observed that hydrogermylation with triphenylgermane and diphenylgermane was possible, which could be extended to a polymerization reaction. Using a small-molecule model system, we demonstrated that Ge–H bonds add to olefins in a 1 : 1 fashion according to a step-growth, radical mediated process, similar to thiol–ene and phosphane–ene systems. This was accomplished using a small amount of initiator under mild conditions, demonstrating the efficiency of this process. The unreacted Ge–H functionality within the polymer network provided a latent handle to perform onwards chemistry, including bond activation, thiolation, and solid-supported germane–ene chemistry. The resulting materials were characterized using EDX, IR, and Raman spectroscopy.